(untitled) - Pimentel, David (Boca Raton, 2002)
Bioinvasion is fast becoming one of the world's most costly ecological problems, as it disrupts agriculture, drastically alters ecosystems, spreads disease, and interferes with shipping. The economic and environmental damages from alien plant, animals, and microbes in the United States, British Isles, Australia, South Africa, India, and Brazil account for more than
Keywords: Biological invasions,Biological invasions; Economic aspects,Environmental aspects